Pelaksanaan Penyidikan oleh Penyidik Polresta Bukittinggi dalam Menetapkan Status Tersangka Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial - Ayudia, Salsa Zhafira; Sukmareni, Sukmareni; Fitri. Z, Yenny (UNES Law Review, 2023)
One form of crime committed in cyberspace (cyber crime) is defamation through social media. One example of a defamation case through social media that occurred in the city of Bukittinggi was addressed to one of the candidates for mayor of Bukittinggi. This case started with a post in the form of a fake letter linking Ramlan Nurmatias with the Indonesian Democratic Party of Struggle. This led to the criminal act of defamation considering that Ramlan Nurmatias was a candidate for mayor from an individual or without any supporting party. The purpose of this research is to find out how the carrying out an investigation by investigators from the Bukittinggi Police in determining the status of a suspect in a criminal act of defamation through social media. The result of this study is the implementation of the investigative process carried out by investigators from the Bukittinggi Police in establishing the status of a suspect in the crime of defamation through social media by involving several related parties in gathering evidence. Obstacles experienced by investigators in carrying out the investigative process require a long time in collecting evidence, obtaining witness statements and investigating investigators in handling cases related to the ITE Law, especially in cases of defamation through social media. Efforts made by investigators to overcome these obstacles, namely by coordinating with the National Police Criminal Investigation Unit in Jakarta in sending evidence carried out at the Jakarta forensic laboratory center, conducting special training for investigators in handling defamation cases through social media and shortening the time during the examination of the witnesses presented.